Controlling factors of organic matter enrichment in continental shale: A case study of the Jurassic Da’anzhai member in the Sichuan Basin - Yao, Yao (Frontiers in Earth Science, 2022)
The continental lake basin is a favorable accumulation area of shale oil and gas, however, the organic matter enrichment regularity in continental lake facies is still controversial, which hinders the exploration of continental shale oil and gas in the Sichuan Basin. In this paper, the relationship between sedimentary environment and organic matter enrichment of continental shale was analyzed by petrology, organic and inorganic geochemistry tests of 153 samples. The results show that different lithologic associations in Da'anzhai member have different contents of organic matter. Among them, the TOC content of unit II (shale-limestone interbed) is the highest, mainly type II kerogen, followed by unit III (shale clip shell limestone belts), mainly type III kerogen. Geochemical indicators show that different paleoenvironmental factors play different leading roles in organic matter enrichment in different periods of Da'anzhai member. Unit Ⅱ is deposited in an arid environment with less fresh water supply, therefore the water cycle is hampered. Due to the effect of salinity stratification, anoxic water was formed, which was beneficial to the preservation of algae and plankton in the lake basin, resulting in the formation of type Ⅱ2 kerogen. Unit III is deposited in a semi-humid and semi-arid climate, and its water is in an oxidizing environment. Precipitation and river runoff increase the input of terrigenous debris and higher plants to form type III kerogen. This study has guiding significance for the cause of organic matter enrichment in Da'anzhai member and the prediction of favorable zones.